Where The Sidewalk Ends: The Governance Of Waterfront Toronto’s Sidewalk Labs Deal - Flynn, Alexandra; Valverde, Mariana (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
In May 2020 Sidewalk Labs, the Google-affiliated ‘urban innovation’ company, announced that it was abandoning its ambition to build a ‘smart city’ on Toronto’s waterfront and thus ending its three-year relationship with Waterfront Toronto. This is thus a good time to look back and examine the whole process, with a view to drawing lessons both for the future of Canadian smart city projects and the future of public sector agencies with appointed boards. This article leaves to one side the gadgets and sensors that drew much attention to the proposed project, and instead focuses on the governance aspects, especially the role of the public ‘partner’ in the contemplated public-private partnership. We find that the multi-government agency, Waterfront Toronto, had transparency and accountability deficiencies, and failed to consistently defend the public interest from the beginning (the Request for Proposals issued in May of 2017).  Because the public partner in the proposed ‘deal’ was not, as is usually the case in smart city projects, a municipal corporation, our research allows us to address an important question in administrative law, namely: what powers should administrative bodies outside of government have in crafting smart city policies?In Canada, the comparatively limited Canadian scholarly work regarding urban law and governance has mainly focused on municipal governments themselves, and this scholarly void has contributed to the fact that the public is largely unaware of the numerous local bodies that oversee local matters beyond municipal governments.  This paper hones into the details of the WT-Sidewalk Labs partnership to understand the powers and limitations of WT in assuming a governmental role in establishing and overseeing ‘smart city’ relationships. It ultimately argues that WT has not been – nor should it be – empowered to create a smart city along Toronto’s post-industrial waterfront. Such tasks, we argue, belong to democratic bodies like municipalities. An important contribution of this paper is to situate the evolving role of public authorities in the local governance literature and in the context of administrative law.